Hysteretic and time dependent deformation of plasma sprayed zirconia ceramics. (1st August 2020) - Lal, Devi; Kumar, Praveen; Sampath, Sanjay; Jayaram, Vikram
Abstract: The effect of microstructural evolution on hysteresis loss and time dependent deformation of air plasma sprayed 7 wt.% Y2 O3 stabilized ZrO2 coating has been studied after isothermal exposure between 800–1300 °C. Miniaturized cantilevers prepared from free-standing heat-treated coatings were loaded using a nanoindenter. Both, the hysteresis loss during cyclic loading and the creep displacement at fixed load show two domains of behavior with respect to heat treatment: a low temperature/time domain wherein the hysteresis loss and the maximum creep displacement drop significantly without measurable change in density, and a high temperature domain in which both parameters decrease more gradually but accompanied by significant densification. Both phenomena are attributed to the partially reversible sliding of interfaces driven by shear stresses that are developed at pores and micro-cracks, as shown by finite element analysis. Phenomenological models are developed to correlate the magnitude of creep displacement with the elastic modulus in the coating, governed primarily by the evolution of inter-splat and inter-columnar porosity Graphical abstract: Image, graphical abstract